Adoption of open access publishing for scholarly communication by academic staff at the University of Limpopo - Shoroma, Moritidi Abigail (My University, 2021)
This study aimed to examine the extent of awareness and the adoption of Open Access (OA) publishing for the purpose of scholarly communication by academic staff at the University of Limpopo (UL). The study was guided by Rogers’ Diffusion of Innovation theory (1) to measure the level of awareness of academics on the availability and use of OA resources; (2) to determine the adoption and usage levels of OA publishing as a platform for information sharing by academics in scholarly communication; (3) to establish academics’ attitudes towards the use of the OA publishing platforms; and (4) to identify perspectives of academic staff with regards to challenges and benefits presented by OA publishing. A dominantly quantitative research approach was adopted using a google forms questionnaire with closed ended questions to collect data from 250 academics at the University of Limpopo. Academics were selected using the systematic simple random sampling method. To ensure the survey instrument’s reliability and validity, the researcher conducted a pilot study through a web-based survey. A descriptive statistics method of the Statistical Package for Social Sciences (SPSS) was used to analyse data. The study established that the majority (82%) of academics were aware of OA publishing platforms. The internet and subject librarians were the main communication channels through which they became aware of OA publishing. The study also found that there was minimal the adoption and usage of OA publishing among academics. Their attitudes towards OA and their perceptions of the benefits and challenges of OA. The general attitudes of academics about OA were positive, signifying the acceptance of this scholarly communication mode. However, some of the challenges encountered in adopting and using OA publishing include slow internet connectivity and access, publication charges by some publishers, lack of skills to publish online, power interruptions, lack of policies on OA, fake and predatory v publishers and OA articles not being peer-reviewed. These were reported as problems that directly or indirectly hinder academics from publishing in OA platforms. The study recommends the institutionalisation of OA publishing at UL to improve research output dissemination. An area for further research will be to establish more insights regarding the feasibility of OA development and possible ways of dealing with article processing fees. Keywords: Open Access publishing, scholarly communication, Academic staff, Institutional Repositories, Rogers’ Diffusion of Innovation theory, University of Limpopo.
Thesis (M.A. ( Information Studies)) -- University of Limpopo, 2021
Keywords: Open Access publishing; Scholarly communication; Academic staff; Institutional Repositories; Rogers’ Diffusion of Innovation theory; University of Limpopo; Electronic information resources -- Access control; Computer network resources; Open access publishing; Institutional repositories